1975
DOI: 10.1577/1548-8659(1975)37[213:teoscf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Six Chemicals for Disinfection of Largemouth Bass Eggs

Abstract: A technique for the controlled incubation of largemouth bass eggs (Micropterus salmonides) has been demonstrated at the Warmwater Fish Cultural Development Center, Marion, Alabama [9]. During the search for an acceptable incubation method, occasional high mortality of embryos was encountered and attributed to disease. Since the brood fish from which the eggs were obtained had a history of chronic hemorrhagic septicemia caused by Aeromonas liquefaciens [8, 10], prophylaxis of the eggs by disinfection (a common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…At higher doses of Buffodine the bactericidal effect was better, but these doses did not have a good safety margin to lethal doses. Toxic effects have previously been observed after 10-15 min treatments with 2 200 mg active iodine 1-l (McFadden, 1969;Wright and Snow, 1975;Subasinghe and Sommerville, 1985). The toxicity of iodophores is pH dependent, i.e.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…At higher doses of Buffodine the bactericidal effect was better, but these doses did not have a good safety margin to lethal doses. Toxic effects have previously been observed after 10-15 min treatments with 2 200 mg active iodine 1-l (McFadden, 1969;Wright and Snow, 1975;Subasinghe and Sommerville, 1985). The toxicity of iodophores is pH dependent, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Because Buffodine is a buffered iodophore designed for use in freshwater, the actual concentrations may have differed from the nominal intended concentrations. Freshwater studies with artificially infected eggs have, however, documented that 10-15 min disinfection with < 200 mg active iodine 1-l do not ensure a total elimination of the epiflora (Wright and Snow, 1975;McCarthy, 1977). Bacteria have also, in agreement with the results here, been reported to be abundant on the surface of red drum eggs (Sciaenops oceflatus L.) after treatment with doses of iodophores that had no adverse effect on larval survival (Douillet and Holt, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the ultraviolet irradiation of water supply during egg incubation and yolk absorption successfully eliminated recurrent motile aeromonad septicemia among muskellunge (Esox masquinongy) fry (Calesante et al 1981). Wright and Snow (1975) found that acriflavine (500-700 mg/l for 15 min) or iodine (100-150 mg/l for 15 min) successfully disinfected eggs of largemouth bass, Micropterus salmoides.…”
Section: Discussionmentioning
confidence: 99%
“…For treatment of largemouth bass Micropterus salmoides eggs, acriflavine (500 to 700 ppm for 15 min) was the disinfectant recommended over 5 other disinfectants by Wright & Snow (1975). Exploration of alternative egg disinfectants may be necessary for prophylaxis against organisms such as Myxobolus cerebralis actinospores that may be carried with eggs into the hatchery.…”
Section: Discussionmentioning
confidence: 99%